2013
DOI: 10.1107/s0108270113025948
|View full text |Cite
|
Sign up to set email alerts
|

Bis[4-amino-N-(pyrimidin-2-yl)benzenesulfonamido]diamminecopper(II): aqua or ammine ligands?

Abstract: Diffraction results obtained at 100 and 291 K, the former at high resolution, are reported for the title compound, [Cu(C10H9N4O2S)2(NH3)2] or [Cu(sulfa)2(NH3)2] [Hsulfa is 4-amino-N-(pyrimidin-2-yl)benzenesulfonamide]. The Cu(II) cation is coordinated by two N-atom donors from a bidentate sulfa ligand, by two ammonia molecules in the equatorial plane and by a monohapto (η(1)) sulfadiazine at the apex of a distorted square pyramid. The present interpretation and two earlier reports [Brown, Cook & Sengier (1987)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…The equatorial bonds of the three complexes are on average of length 2.0 Å. This is consistent with bond lengths of copper(II)-sulfonamide-(N^N) in ternary complexes reported in the literature [24,[39][40][41]. The copper(II)-N phen values observed for complexes 1 and 2 are within the range of short lengths for such bonds (< 2.05 Å) [42].…”
Section: X-ray Crystallographic Studiessupporting
confidence: 88%
See 1 more Smart Citation
“…The equatorial bonds of the three complexes are on average of length 2.0 Å. This is consistent with bond lengths of copper(II)-sulfonamide-(N^N) in ternary complexes reported in the literature [24,[39][40][41]. The copper(II)-N phen values observed for complexes 1 and 2 are within the range of short lengths for such bonds (< 2.05 Å) [42].…”
Section: X-ray Crystallographic Studiessupporting
confidence: 88%
“…Beloso et al reported crystal structures of similar complexes in which axial CueN interactions were of the order of 2.5 Å [39]. The copper(II) complex with sulfadimethoxine and ammonia molecules instead of a (N^N) ligand, previously reported in the literature, was clearly a 5-coordinate complex, since the sixth theoretical axial CueN "bond" is longer than 3.0 Å [24,40]. The copper complexes with benzothiazole-derived sulfonamides showed a similar coordination geometry to the complexes of this work, but the axial bond lengths longer than 2.8 Å were not considered effective bonds by the authors [10].…”
Section: X-ray Crystallographic Studiesmentioning
confidence: 78%